The Model of Buddhist Innovation for Cultivating a Positive Conciousness Among the New Generation to Resolve Political Conflicts in Democratic System of The Central North-eastern Region - Pochailar, Pornpimol (Dhammathas Academic Journal, 2025)
This research aims to: 1) examine the conditions of organizing processes that cultivate positive awareness among the younger generation for resolving political conflicts within the democratic system in the central northeastern region of Thailand; 2) develop a Buddhist innovation model to foster such awareness; and 3) present the outcomes of implementing this model. A mixed-methods approach was employed. The quantitative component involved a survey conducted with 400 participants, while the qualitative component involved focus group discussions and consensus-based decision-making with five experts. Data analysis included means, percentages, standard deviations, statistical tests, correlation coefficients, and descriptive analysis. The research findings are as follows: 1. Political conflicts were identified in five major domains: informational, value-based, relational, interest-related, and structural. Each domain was characterized by specific indicators. Conflict resolution strategies were grounded in Buddhist principles—for example, Yoniso Manasikara was used to address informational conflicts, Iddhipada 4 for value-based and relational conflicts, Kalyāṇamitta for interest-related conflicts, and the Threefold Training (Trisikkhā) for structural conflicts. 2. The quantitative results demonstrated a statistically significant improvement in democratic attitudes following the implementation of the Buddhist innovation model. The average score increased from 3.25 to 3.89 (p < 0.05). Moreover, the target group showed improved understanding of Buddhist principles, greater tolerance for differing opinions, and a reduction in violent behavior—all key factors in mitigating political conflict. These findings underscore the effectiveness of Buddhist innovations in cultivating positive awareness and promoting sustainable conflict resolution in Thai society. 3. The application of the Buddhist innovation model led to the production of 100 manuals and academic dissemination through various formats.